Preparation of zinc layered hydroxide-ferulate and coated zinc layered hydroxide-ferulate nanocomposites for controlled release of ferulic acid. (7th June 2019) - Hashim, Norhayati; Sharif, Sharifah Norain Mohd; Muda, Zuhailimuna; Md Isa, Illyas; Ali, Noorshida Mohd; Bakar, Suriani Abu; Sidik, Siti Munirah; Hussein, Mohd Zobir
Abstract: Ferulic acid (FA) was intercalated into zinc layered hydroxide (ZLH) to form a new nanocomposite, namely zinc layered hydroxide-ferulate (ZLH-FA) and was further coated by surfactants sodium dodecyl sulfate (SDS) and polysorbate 80 (Tween-80). XRD patterns of the ZLH-FA nanocomposite obtained reveals a crystalline structure with basal spacing of 26·9 Å. The XRD pattern of the coated nanocomposite showed similar peaks to the ZLH-FA nanocomposite. The loading of FA in the nanocomposite was estimated to be 56·82% (w/w), and its thermal stability was markedly enhanced compare to its free counterpart. A controlled release study showed that the FA was release was slower from interlayer of ZLH-FA/SDS and ZLH-FA/Tween-80 nanocomposites compared to the ZLH-FA nanocomposite. The mechanism of release follow the pseudo-second order kinetics model for all nanocomposites. Results from this study highlight the potential of these nanocomposites for controlled release formulation of FA drug anion.